Manajamen Strategi Badan Penanggulangan Bencana Daerah dalam Penanganan Banjir di Desa Wanajaya Kecamatan Cibitung Kabupaten Bekasi - Bayu Mahardika; Dadan Kurniansyah; Sopyan Resmana Adiarsa (Jurnal Ilmiah Wahana Pendidikan, 2022)
A disaster is an event or series of events that threatens and disrupts people's lives and livelihoods caused by both natural and non-natural factors as well as human factors, resulting in human casualties, environmental damage, property losses, and psychological impacts. The most frequent disasters in Indonesia with high rainfall intensity can cause floods. A flood is a disaster caused by the inundation of water in an area with a long period span. Wanajaya Village is an area that often experiences flooding every year due to its low topography and narrow river flow. The Regional Disaster Management Agency of Bekasi Regency became the topic of research to conduct a study on strategic management in tackling flood disasters in Wanajaya Village, Cibitung District. Strategic management is carried out by referring to the concept of Fred R. David in the method of formulating a strategy. Strategic analysis conducted by BPBD Bekasi Regency from strategy formulation, strategy implementation, and strategy evaluation. The results of this study indicate that strategic management in implementation must be realized immediately and the evaluation of BPBD Bekasi Regency must be carried out periodically and continuously. With the identification and in-depth analysis of the management of flood disaster management strategies in Wanajaya Village. Can mitigate and prevent flood disasters and reduce the impact of the flood disaster.